Antioxidant Activity of Ethanolic Extract from Tandui Leaves (Mangifera rufocostata Kosterm.) by DPPH Radical Scavenging Method - Revita Saputri; Tia Mariati Risma Melati; Fitriyanti Fitriyanti (Borneo Journal of Pharmacy, 2019)
Tandui (Mangifera rufocostata Kosterm.) is a typical plant from South Kalimantan which belongs to the genus of Mangifera. Several species of Mangifera are known to have antioxidant activity. This study aimed to determine the antioxidant activity of ethanol extract of Tandui leaves. Tandui leaves that were obtained from the maceration method used 70% ethanol. Antioxidant activity was conducted quantitative using the DPPH (2,2-diphenyl-1-picrylhydrazil) method. The result of the antioxidant activity of Ethanol extract of Tandui leaves quantitatively obtained IC50 value was 60.7042 µg/mL. The ethanol extract of Tandui leaves has strong antioxidant activity